Persistently Elevated Risk of Syphilis Among Human Immunodeficiency Virus-Positive Men Receiving Care in a Status-Neutral Setting: A Retrospective Analysis. Issue 3 (2nd March 2023) - Shalev, Noga; Castor, Delivette; Morrison, Ellen; Quigee, Daniela; Huang, Simian; Zucker, Jason
Abstract : Among men participating in a status-neutral comprehensive human immunodeficiency virus program in New York City, human immunodeficiency virus-positive status was associated with higher odds of early syphilis, but not of chlamydia or gonorrhea. Abstract : Background: Over the past decade, the incidence of primary and secondary syphilis has increased dramatically in the United States and Western Europe. Men living with human immunodeficiency virus (HIV) and those at risk of HIV infection experience disproportionately high rates of early syphilis (ES). We compared the odds of ES among HIV-positive and HIV-negative men participating in a status-neutral comprehensive HIV prevention and treatment program (CHP). Methods: We conducted a retrospective analysis of men aged 18 to 65 years with ≥ 1 CHP visit and ≥2 rapid plasma reagin (RPR) tests performed between January 1, 2018, and December 31, 2021. Early syphilis was defined as newly reactive RPR with a minimum titer of ≥1:4 or a ≥ 4-fold increase in the RPR titer. Multiple logistic regression analyses were performed to determine predictors of ES. Results: A total of 2490 men met the inclusion criteria, of whom 1426 (57.3%) were HIV-positive and 1064 (42.7%) were HIV-negative. Of the 393 men with ES, 284 (72.3%) were HIV-positive and 109 (27.7%) were HIV-negative. Human immunodeficiency virus-positive men had higher adjusted odds of ES (adjusted odds ratio, 2.86; 95% confidence interval, 2.45–3.27) than HIV-negative men did. Chlamydia or gonorrhea infection did not differ according to HIV status (adjusted odds ratio, 0.93; 95% confidence interval, 0.82–1.04). Conclusions: In our status-neutral care setting, HIV-positive status was associated with significantly higher odds of ES, but not chlamydia or gonorrhea. Our findings emphasize the vulnerability of HIV-positive men to syphilis in an era of effective HIV biomedical prevention.